Stage protocol in the management of infection following plating of the tibia - Mohd Yusof, Nazri; Halim, A. S. (Faculty of Medicine, International Islamic University Malaysia, 2012)
Introduction: Anterior border of the tibia is covered only by a thin layer of protective tissue. Plating of the tibia often results in wound complication and infection if the injury to this area is not recognized. We review our results of managing infection following plating of the tibia using a protocol base on the status of bone healing and the presence of bone or soft-tissue defect. Methods: Eight cases of infection following plating of the tibia were managed according to stage procedures protocols and classification, which is based on the state of bony union and the defect following wound debridement. The soft-tissue defects were managed with local flaps, and the bone defects were managed with Illizarov bone transport. Results: Three patients had more than one bacterium isolated. Gram negative organisms were isolated from seven patients. Methicillineresistant Staphylococcus aureus was isolated in two patients. All patients achieved union with a mean union time of seven months. The infections were controlled in seven patients. One patient had minimal sinus discharge but refused further treatment. Conclusions: The stage protocol for the management of infection following plating of the tibia is practical and produces excellent results.